The Influence of Social Media Marketing and Product Quality on Brand Awareness and Purchase Decisions on Skintific Products in Pekanbaru City - Raesela, Raesela; Jushermi, Jushermi; Noviasari, Henni (West Science Business and Management, 2024)
This study aims to see the influence of Social Media Marketing and product quality on brand awareness and purchase decisions on Skintific products in Pekanbaru City. This study was conducted in Pekanbaru City. The population in this study were the people of Pekanbaru City who bought Skintific products. The number of samples in this study was 175 people. The number of samples in this study was carried out using the non-probability sampling technique with the purposive sampling technique, namely sampling based on certain considerations. The results of the study found that: 1.) Social Media Marketing has a significant effect on purchase decisions. 2.) Product quality has a significant effect on purchase decisions. 3.) Social media marketing has a significant effect on brand awareness. 4.) Product quality has a significant effect on brand awareness. 5.) Brand awareness has a significant effect on purchase decisions. 6.) Social media marketing has a significant effect on purchase decisions moderated by brand awareness. 7.) Product quality has a significant effect on purchase decisions moderated by brand awareness.